Significance of Carotid Canal Plasticity and the RNF213 p.R4810K Mutation in Distinguishing Moyamoya Disease From Middle Cerebral Artery Disease. (16th November 2020) - Oichi, Yuki; Mineharu, Yohei; Morimoto, Takaaki; Agawa, Yuji; Funaki, Takeshi; Hitomi, Toshiaki; Kobayashi, Hatasu; Todo, Kenichi; Tani, Shoichi; Imamura, Hirotoshi; Koizumi, Akio; Sakai, Nobuyuki; et al.
Abstract: INTRODUCTION: Difference between moyamoya disease (MMD) and middle cerebral artery disease (MCAD) is not necessarily clear. METHODS: Eighty-five MMD patients, 27 MCAD patients and 79 controls were recruited. Outer diameter of carotid arteries were assessed by the carotid canal diameter (CCD) in thin slice CT and/or direct measurement by high resolution MRI. The p.R4810K genotyping was performed by TaqMan probes. To assess plasticity of bony carotid canal, serial measurement of carotid canal was done in 8 individuals who received carotid artery ligation. RESULTS: CCD showed significant correlation with the outer diameter of internal carotid arteries. CCD was significantly narrower in females than in males ( P < .01) and in children than in adults ( P < .01), whereas the p.R4810K mutation did not affect the diameter. CCD was significantly narrower in patients with MMD than in controls, and a cut-off value of 5.0 mm for adult men and 4.5 mm for adult women and children was best to discriminate patients from controls, with the sensitivity of 0.82 and the specificity of 0.92. When carotid canal stenosis and the p.R4810K mutation were combined, the both positive populations accounted for 68.3% in MMD and only 1.9% in MCAD. Bony carotid canal got narrower after the carotid artery ligation and the diameter in MMD patients showed negative correlation with Suzuki's stage, suggesting the plasticity of bony carotid canal. CONCLUSION: Combination of narrow carotid canal and the p.R4810K mutation was useful to distinguish MMD and MCAD. As bony carotid canal was shown to be remodeled, it is likely to be a result of inward arterial remodeling rather than a cause of narrow outer diameter.